Microsoft Windows 10 tutorial : essential video guide to mastering Windows 10 (Que, 2015)
"This video course also includes more advanced information to help users truly be able to customize Windows 10 to their personal and/or professional preferences. This video series is designed to help you to install and use Windows 10. Technology and Microsoft MVP, Brien Posey, demonstrates how to install Windows 10 and how to upgrade existing Windows PCs and tablets. Posey also demonstrates how to use a wide variety of Windows 10 features and even how to use the new operating system on a phone or tablet. Whether you are just getting started with Windows or you have used other versions of Windows for years, this video series is for you."--Resource description page.